(untitled) (Journal of the College of Education for Women, 2019)
There is no doubt that leadership is a social phenomenon , and human activity does not take place , but remained in the family cohesive have a common goal Alaho instil confidence in the same of her sons to be better , and the importance of this subject Arta researchers to identify the extent to which children in this phenomenon and to identify the causes and extent of its spread in the community , has been directing an open question (Appendix 1) to a group of kindergarten teachers , to learn about the characteristics of leadership that can be enjoyed by kindergarten children . The current research aims to:1. Detect levels of leadership qualities among kindergarten children in the light of the characteristics of leadership skills2. Identify the characteristics of leadership on the children of kindergarten age ( 4-6 years).The sample consisted of 160 children and child. Find and identify with that of children in the city of Riyadh, Baghdad Rusafa second breeding . Was used in the search with the help of statistical methods bag statistical SPSS. The research includes recommendations and proposals of the task.The most important final results: There are no statistically significant differences in the mean scores of children aged (4-5 years) years (total sample) on a tool to measure characteristics of leadership at the level of significance ( 0.05).